ENZYMO- ROCKET ELECTROPHORETIC ASSAY AND CROSSED AFFINITY ENZYMOIMMUNOELECTROPHORESIS AND ITS APLICATION IN DIAGNOSIS OF PLIMARY LIVER CANCER - Huang, Hua; Liao, Zhaoquan; Huang, Jiqun; Huang, Wei (Chinese Journal of Cancer Research, 2013)
A sensitive and accurate quantitative method of alphafetoprotein (AFP), enzymo-rocket dectrophoretie assay (EREA), was developed by introducing horseradish peroxidase-labeled anti-btmmn AFP antibody into rocket electrophoresis. The lower limit of quantitation by this method is about 10 ng/ml of AFP. The dose-nesponse curve covers a broader range of concentrations of AFP (10--4000 ng/ml) than RIA (0---400 ng/ml). 3fine accm-acy and precision is comparable to that of RIA (r=0.986). Sermn AFP measured in 100 patients with primary liver cancer by this method, 88% had levels over 25 ng/ml. The crossed affinity enzymoimmtmoelectrophoresis is a combination of lentil lectin (LCA) affinity electrophoresis and enzymo-rocket electrophoresis, it has been possible to separate the AFP into two variants, LCA-reactive (LCA-R) and LCA-nonreactive (LCA-N) fractions. The advantages of this method are high sensitivity, rapid (6--7 h), and can be effectively used to differentiate the primary liver cancer and benign liver disease.